Consultation liaison psychiatry in Sri Lanka: a case for sub-specialisation - Hanwella, Raveen (Sri Lanka Journal of Psychiatry, 2010)
Liaison psychiatry has not been established in Sri Lanka as a sub-speciality. However many psychiatrists who work in general hospital settings are required to do liaison work. Patterns of referrals to a university psychiatry liaison unit were studied in order to identify the requirements in training for liaison psychiatry in Sri Lanka. A retrospective analysis of records of all new patients registered during a six month period from 1st January 2010 in the liaison unit of the University Psychiatry Unit, Colombo was carried out. A total of 1079 patients were referred to the liaison unit during this period. The commonest reason for referral was assessment of patients who were admitted to medical or surgical wards after deliberate self harm. The variety of clinical conditions referred to liaison units highlight that psychiatry trainees need a broad knowledge of general medicine and a wide repertoire of clinical and other skills to effectively manage their patients. Specialised liaison units should be started in the general hospitals and should form the nucleus for training and establishing the field of consultationliaison psychiatry as a subspecialty in Sri Lanka.
Keywords: MEDICINE::Psychiatry; Sri Lanka